2019
DOI: 10.1186/s12870-019-2184-1
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the photosynthetic and physiological responses of Leymus chinensis to different levels of grazing intensity

Abstract: BackgroundGrazing is an important land use in northern China. In general, different grazing intensities had a different impact on the morphological and physiological traits of plants, and especially their photosynthetic capacity. We investigated the responses of Leymus chinensis to light, medium, and heavy grazing intensities in comparison with a grazing exclusion control.ResultsWith light grazing, L. chinensis showed decreased photosynthetic capacity. The low chlorophyll and carotenoid contents constrained li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 91 publications
1
22
1
Order By: Relevance
“…This is in accordance with the results of P n ( Figure 2 A). Liu et al have found that lower quantities of the photosynthetic pigments may inhibit the photosynthetic capacity [ 26 ]. The results showed that HT stress reduced Chl contents in the leaves of S. calendulacea ( Figure 1 B–F) and limited the absorption of light energy [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with the results of P n ( Figure 2 A). Liu et al have found that lower quantities of the photosynthetic pigments may inhibit the photosynthetic capacity [ 26 ]. The results showed that HT stress reduced Chl contents in the leaves of S. calendulacea ( Figure 1 B–F) and limited the absorption of light energy [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In view of the confirmation of photosynthetic activity in both cotyledon types, we expected that the quantum yield would be higher in albino plant cotyledons, which would represent a metabolic compensation for the photosynthetic inefficiency of its leaves. Photosynthetic compensation has been reported for plant leaves under various environmental conditions or stresses (Rivas et al 2017;Liu et al 2019), being one way to optimize performance of photosynthetic metabolism. However, this hypothesis was not corroborated for D. regia, and the values of F v /F m and (F 0 m -F 0 )/F 0 m were similar in cotyledons of both albino and WT seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…Photosynthetic compensation has been reported for plant leaves under various environmental conditions or stresses (Rivas et al . 2017; Liu et al 2019), being one way to optimize performance of photosynthetic metabolism. However, this hypothesis was not corroborated for D. regia , and the values of F v /F m and ( F′ m – F′ )/ F′ m were similar in cotyledons of both albino and WT seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…The ultrastructure of the leaf cells was measured according to the methods described by Liu et al [ 100 ], with minor modification. Leaf samples were cut into small pieces (about 1 cm × 1 cm) and fixed in 2.5% glutaraldehyde solution at 4 °C.…”
Section: Methodsmentioning
confidence: 99%